Iron deposition in the precuneus is correlated with mild cognitive impairment in patients with cerebral microbleeds: A quantitative susceptibility mapping study - Tu, Jing; Yan, Jin; Liu, Juan; Liu, Dandan; Wang, Xiaomeng; Gao, Fei (Frontiers in Neuroscience, 2022)
Purpose: To define whether mild cognitive impairment is associated with iron deposition in rich club nodes distant from cerebral microbleeds in patients with cerebral small vessel disease. Methods: A total of 64 participants underwent magnetic resonance imaging scanning, and were separated into three groups: CMB(+), CMB(−), and healthy controls. We compared their characteristics and susceptibility values of rich club nodes (including superior frontal gyrus, precuneus, superior occipital gyrus, thalamus, and putamen). We then divided the CMB(+) and CMB(−) groups into subgroups of patients with or without mild cognitive impairment. Next, we analyzed the relationship between iron deposition and mild cognitive impairment by comparing the susceptibility values of rich club nodes. We assessed cognitive functions using the Montreal Cognitive Assessment and quantified iron content using quantitative susceptibility mapping. Results: In the putamen, the CMB(+) and CMB(−) groups had significantly different susceptibility values. Compared with the healthy controls, the CMB(+) and CMB(−) groups had significantly different susceptibility values for the superior frontal gyrus and superior occipital gyrus. In addition, we found significant differences in the putamen susceptibility values of the CMB(+)MCI(+) group and the two CMB(−) groups. The CMB(+)MCI(+) and CMB(+)MCI(−) groups had significantly different precuneus susceptibility values. The binary logistic regression analysis revealed that only higher susceptibility values of precuneus were associated with a cognitive decline in patients with cerebral microbleeds, and it indicated statistical significance. Conclusion: Iron deposition in the precuneus is an independent risk factor for mild cognitive impairment in patients with cerebral microbleeds. Cerebral microbleeds might influence iron content in remote rich-club nodes and be relevant to mild cognitive impairment.